Statistics Kingdom: A Very Helpful Basic Statistical Analysis Tool for Health Students - Tanko Titus Auta; Heru Santoso Wahito Nugroho; Gede Dalem Gilang Mahajaya Putra; Ketut Sudiantara; I Ketut Gama; I Wayan Mustika; Suparji Suparji; Fransiskus Salesius Onggang; Wayan Rusni; Tanjung Subrata; Trisna Sumadewi; Sanglar Polnok; Matje Meriati Huru; Kamilus Mamoh; Jane Leo Mangi; Tri Johan Agus Yuswanto (Humanistic Network for Science and Technology (HNST), 2022)
“Statistics Kingdom” is a website that really helps the learning process of “statistics and research” for health students. When final year health students need statistical analysis tools for their research projects, then visiting the “Statistics Kingdom” website is a very good choice. Health students can very easily enter data and then analyze it directly on the website, also provided the opportunity to ask questions and discuss further with the consultant. Thus, “Statistics Kingdom” is a web-based statistical analysis tool that health students really need.Keywords: “Statistics Kingdom”; statistical analysis; website